Negative pole piece for secondary battery, preparation method and secondary battery

By covering the surface of the negative electrode active material of the negative electrode sheet with lithium carboxylate-based polyether to form a network structure, the gas production and SEI film rupture of the high-silicon system negative electrode material during high-temperature cycle is solved, and the long cycle of the battery is significantly improved performance.

CN119495697APending Publication Date: 2025-02-21NIO BATTERY TECH (ANHUI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311029340.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-14
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing high-silicon system anode materials are prone to gas production, SEI film rupture and generation during high temperature cycles, resulting in a shortened battery life and a reduced application environment.

Method used

The surface of the negative electrode active material of the negative electrode sheet is coated with lithium carboxylate-based polyether to form a network structure to block HF and PF5 in the electrolyte, and inhibit the rupture and side reaction of the silicon material.

Benefits of technology

It effectively improves the SEI film on the surface of the negative electrode material layer, reduces the gas production reaction at high temperatures, and extends the long circulation performance of the negative electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004397777360000021
    Figure BDA0004397777360000021
  • Figure BDA0004397777360000054
    Figure BDA0004397777360000054
  • Figure BDA0004397777360000131
    Figure BDA0004397777360000131
Patent Text Reader

Abstract

The invention relates to a negative electrode plate for a secondary battery, the negative electrode plate comprises a negative electrode current collector and a negative electrode material layer, the negative electrode material layer is arranged on the surface of the negative electrode current collector, and the negative electrode material layer comprises a negative electrode active material and carboxylic acid lithium-based polyether. According to the lithium carboxylate-based polyether, a three-dimensional network is formed on the surface of a negative electrode active material, so that the problem of gas production during high-temperature storage is solved, cracking of silicon in the negative electrode material can be inhibited, and side reactions are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of secondary battery materials, and in particular to a negative electrode sheet for a secondary battery, a preparation method, and a secondary battery. Background Art

[0002] New energy vehicles have increasingly higher requirements for the energy density of secondary batteries. High-energy-density secondary battery positive electrodes generally use high-nickel ternary materials, and negative electrodes use silicon-graphite composite negative electrode materials. On the one hand, conventional silicon-graphite negative electrodes are prone to gas production when used at high temperatures, especially when the silicon content is relatively high, the gas production phenomenon is more serious, and battery bloating will also lead to the risk of battery leakage; on the other hand, during high-temperature cycling, the volume change of silicon materials leads to the rupture and generation of SEI, which increases the reaction activity with the electrolyte. At the same time, the electrolyte will decompose at high temperatures to produce HF, PF5 and other products, which can destroy silicon materials. The above problems greatly reduce the service life of the battery and the application environment range of silicon-based negative electrode secondary batteries, causing the battery capacity to decay rapidly. Therefore, it is urgent to improve the long-cycle performance of high-silicon system negative electrodes. Summary of the invention

[0003] In view of the problems existing in the prior art, the present invention improves the SEI film on the surface of the negative electrode material layer by coating the surface of the negative electrode active material of the negative electrode plate with a carboxylic acid lithium polyether, which is beneficial to improve the gas production problem during high-temperature storage. At the same time, it can inhibit the decomposition of silicon in the negative electrode material, reduce side reactions, and improve the long cycle performance of the negative electrode.

[0004] The first aspect of the present disclosure provides a negative electrode plate, the negative electrode plate comprising a negative electrode current collector; and a negative electrode material layer, the negative electrode material layer is disposed on the surface of the negative electrode current collector, the negative electrode material layer comprises a negative electrode active material and a lithium carboxylate polyether. The lithium carboxylate polyether is present on the surface of the negative electrode active material.

[0005] In one aspect of the present disclosure, the structure of the lithium carboxylate polyether is as shown in Formula I:

[0006]

[0007] Wherein, n=5-100, m=5-50; R 1 , R 2 Each is independently selected from C2-C20 alkenyl, propylene carbonyl, methyl propylene carbonyl, C2-C3 epoxy; R 3 , R 4 , R 5 Each is independently selected from a hydrogen atom, a methyl group, and an ethyl group.

[0008] A second aspect of the present disclosure provides a method for preparing a negative electrode sheet, characterized in that the method comprises:

[0009] S1: mixing a binder, a first solvent and a negative electrode active material, stirring them evenly to obtain a slurry, and coating the slurry on the surface of a negative electrode current collector to obtain a first negative electrode sheet;

[0010] S2: rolling the first negative electrode sheet to a suitable compaction density, and obtaining a second negative electrode sheet after a first drying;

[0011] S3: dissolving carboxylic acid lithium polyether, lithium salt and initiator in a second solvent to obtain a mixed solution, and then coating the mixed solution on the surface of the second negative electrode plate away from the current collector, and after a second drying, obtaining the negative electrode plate.

[0012] A third aspect of the present disclosure provides a secondary battery, which includes the aforementioned negative electrode sheet or the negative electrode sheet prepared by the aforementioned preparation method.

[0013] A fourth aspect of the present disclosure provides a device, which includes the aforementioned secondary battery.

[0014] Beneficial effects:

[0015] The present disclosure provides a negative electrode plate, the surface of which is coated with a carboxylic acid lithium-based polyether, and the groups at both ends of the carboxylic acid lithium-based polyether are cross-linked on the surface of the negative electrode active material to form a network structure. On the one hand, the network structure can block the damage of HF and PF5 in the electrolyte to the negative electrode active material, reducing the gas production reaction at high temperature; on the other hand, due to the wrapping of the network structure, the rupture of the silicon negative electrode material due to volume expansion during the cycle is suppressed, and the long cycle performance is extended. The lithium carboxylate in the carboxylic acid lithium-based polyether can interact with silicon, so that the carboxylic acid lithium-based polyether is anchored on the surface of the negative electrode active material, and the polyether plays a connecting role, which inhibits the cracking of silicon to a certain extent, reduces the formation of SEI film, and inhibits side reactions such as gas production. The polyether in the carboxylic acid lithium-based polyether has lithium conductivity, which is beneficial to the ion transmission of the negative electrode plate, and it is stable and not easy to decompose on the negative electrode surface, preventing the thickening of the SEI film from causing the impedance of the battery cell to increase. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.

[0017] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0018] In this article, the terms "comprises", "comprising" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprising a ..." does not exclude the presence of other identical elements in the process, method, article or device that includes the element.

[0019] In the description herein, unless otherwise specified, “above” and “below” include the number.

[0020] In this article, unless otherwise specified, the terms used in the present disclosure have the well-known meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the various parameters mentioned in the present disclosure can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of the present disclosure).

[0021] As used herein, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0022] In this article, the selection range of the terms "and / or", "or / and", and "and / or" includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the arbitrary and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or", "or / and", and "and / or", it should be understood that the technical solution undoubtedly includes technical solutions that are all connected by "logical and", and undoubtedly includes technical solutions that are all connected by "logical or". For example, "A and / or B" includes three parallel solutions of A, B and A+B. For example, the technical solution of "A, and / or, B, and / or, C, and / or, D" includes any one of A, B, C, and D (that is, the technical solution that is all connected by "logical OR"), and also includes any and all combinations of A, B, C, and D, that is, the combination of any two or any three of A, B, C, and D, and also includes the combination of four of A, B, C, and D (that is, the technical solution that is all connected by "logical AND").

[0023] In this document, "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features.

[0024] As used herein, the term "alkenyl" refers to a hydrocarbon group containing at least one carbon-carbon double bond. Examples of the term "alkenyl" used in the chemical formula are ethenyl, propenyl, isopropenyl, cyclopropenyl, butenyl, isobutenyl, tert-butenyl, cyclobutenyl, and the like.

[0025] As used herein, the term "propylene carbonyl" refers to

[0026] As used herein, the term "methacrylic carbonyl" refers to

[0027] In this document, the term "C2-C3 epoxy group" refers to

[0028] The present disclosure is further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present disclosure and are not used to limit the scope of the present disclosure. Specific implementation method:

[0030] In some embodiments of the present disclosure, the negative electrode sheet involved in the present disclosure includes a negative electrode current collector and a negative electrode material layer, wherein the negative electrode material layer is disposed on the surface of the negative electrode current collector, and the negative electrode material layer includes a negative electrode active material and a lithium carboxylate polyether. The lithium carboxylate polyether is present on the surface of the negative electrode active material.

[0031] In some embodiments of the present disclosure, the structure of the lithium carboxylate polyether is as shown in Formula I:

[0032]

[0033] Wherein, n=5-100, m=5-50; R 1 , R 2 Each is independently selected from C2-C20 alkenyl, propylene carbonyl, methyl propylene carbonyl, C2-C3 epoxy; R 3 , R 4 , R 5 Each is independently selected from a hydrogen atom, a methyl group, and an ethyl group.

[0034] In some embodiments of the present disclosure, the lithium carboxylate polyether includes at least one of the following structures:

[0035] Formula I-1 Wherein, n=6-20, m=8-30;

[0036] Formula I-2 Wherein, n=6-20, m=8-30;

[0037] Formula I-3 Among them, n=6-20, m=8-30.

[0038] In some embodiments of the present disclosure, based on the total mass of the negative electrode material layer, the mass percentage of the lithium carboxylate-based polyether is 0.5%-6%.

[0039] In some embodiments of the present disclosure, the specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. In some embodiments of the present disclosure, the negative electrode active material includes at least one of silicon-based materials, carbon-based materials, tin-based materials, phosphorus-based materials, and metallic lithium. The silicon-based material includes at least one of silicon, silicon alloys, silicon oxide compounds, and silicon carbon compounds. The carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, and graphene. The tin-based material includes at least one of tin, tin oxide, and tin alloys. The phosphorus-based material includes phosphorus and / or phosphorus complexes. In some embodiments of the present disclosure, the negative electrode active material is a mixture of silicon-carbon compounds or silicon dioxide and graphite.

[0040] In some embodiments of the present disclosure, the mass percentage of silicon in the silicon-carbon compound is 5%-40%; in some embodiments of the present disclosure, the mass percentage of silicon oxide in the mixture of silicon oxide and graphite is 5%-40%.

[0041] In some embodiments of the present disclosure, based on the total mass of the negative electrode material layer, the mass proportion of the negative electrode active material is 90% to 96%.

[0042] In some embodiments of the present disclosure, the negative electrode material layer further comprises a binder, and the mass percentage of the binder is 0.3%-5% based on the total mass of the positive electrode material layer. The binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector.

[0043] In some embodiments of the present disclosure, non-limiting examples of the binder include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.

[0044] In some embodiments of the present disclosure, the binder is a mixture of styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) and polyacrylic acid (PAA), and the mass ratio of SBR:CMC:PAA is (0.5% to 3%):(1% to 3%):(1% to 3%).

[0045] In some embodiments of the present disclosure, the negative electrode material layer may further include a conductive agent, and the mass percentage of the conductive agent is 0.3%-3% based on the total mass of the positive electrode material layer. The conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0046] In some embodiments of the present disclosure, the negative electrode current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof. In some embodiments of the present disclosure, the negative electrode current collector is copper foil.

[0047] The present invention also provides a method for preparing a negative electrode sheet. In some embodiments of the present disclosure, a method for preparing the negative electrode sheet includes:

[0048] S1: mixing a binder, a first solvent and a negative electrode active material, stirring them evenly to obtain a slurry, and coating the slurry on the surface of a negative electrode current collector to obtain a first negative electrode sheet;

[0049] S2: rolling the first negative electrode sheet to a suitable compaction density, and obtaining a second negative electrode sheet after a first drying;

[0050] S3: dissolving carboxylic acid lithium polyether, lithium salt and initiator in a second solvent to obtain a mixed solution, and then coating the mixed solution on the surface of the second negative electrode plate away from the current collector, and after a second drying, obtaining the negative electrode plate.

[0051] In some embodiments of the present disclosure, the first solvent is water and / or N-methylpyrrolidone (NMP). In some embodiments of the present disclosure, the first solvent is water.

[0052] In some embodiments of the present disclosure, the compacted density is 1.5 g / cm 3 -1.7g / cm 3 .

[0053] In some embodiments of the present disclosure, the first drying is vacuum drying, the drying temperature is 70-120° C., and the drying time is 12-48 hours.

[0054] In some embodiments of the present disclosure, the moisture content of the second negative electrode plate is less than 150 ppm.

[0055] In some embodiments of the present disclosure, the second solvent includes at least one of methyl formate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, butyl acetate, ethyl butyrate, dimethyl ether, butyl ether, toluene, and acetonitrile.

[0056] In some embodiments of the present disclosure, the moisture content of the second solvent is less than 10 ppm.

[0057] In some embodiments of the present disclosure, the solid content of the mixed solution is 3%-20%.

[0058] In some embodiments of the present disclosure, the second drying is vacuum drying at a drying temperature of 60°C-110°C.

[0059] In some embodiments of the present disclosure, the initiator is azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate. In some embodiments of the present disclosure, based on the mass of the lithium carboxylate polyether, the added amount of the initiator is 0.05%-0.5%.

[0060] In some embodiments of the present disclosure, the lithium salt is at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium difluorophosphate, and lithium difluorooxalatoborate. In some embodiments of the present disclosure, based on the total mass of the negative electrode material layer, the mass proportion of the lithium salt is 0.2%-2%.

[0061] The present invention also provides a secondary battery, which comprises the aforementioned negative electrode plate or the negative electrode plate prepared by the aforementioned preparation method.

[0062] In some embodiments of the present disclosure, the secondary battery provided by the present disclosure further includes a positive electrode plate, and the positive electrode plate includes a positive electrode collector and a positive electrode material layer disposed on the positive electrode collector.

[0063] In some embodiments of the present disclosure, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material may include a composite oxide, the composite oxide containing lithium and at least one element selected from cobalt, manganese and nickel. The specific types of the positive electrode active materials are not subject to specific restrictions and can be selected according to needs. The positive electrode active material includes lithium cobalt oxide LiCoO 2 (LCO), at least one of lithium nickel manganese cobalt ternary material (NCM), lithium iron phosphate, and lithium manganese oxide.

[0064] In some embodiments of the present disclosure, the positive electrode material layer further comprises a binder, and the mass percentage of the binder is 0.3%-5% based on the total mass of the positive electrode material layer. In some embodiments of the present disclosure, non-limiting examples of the binder include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin, nylon, etc., but are not limited thereto.

[0065] In some embodiments of the present disclosure, the positive electrode material layer further includes a conductive agent, and the mass percentage of the conductive agent is 0.3%-3% based on the total mass of the positive electrode material layer. In some embodiments of the present disclosure, the conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive agents include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof, but are not limited thereto.

[0066] In some embodiments of the present disclosure, the positive electrode current collector may be aluminum (Al), but is not limited thereto.

[0067] In some embodiments of the present disclosure, a separator is provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the secondary battery of the present disclosure are not particularly limited, and can be any technology disclosed in the prior art.

[0068] In some embodiments of the present disclosure, the separator includes a polymer or an inorganic substance, etc., formed of a material that is stable to the electrolyte of the present disclosure.

[0069] In some embodiments of the present disclosure, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide.

[0070] Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.

[0071] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.

[0072] The inorganic layer includes inorganic particles and a binder, wherein the inorganic particles include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0073] The polymer layer contains polymers, and the polymer material includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).

[0074] The secondary battery according to the present disclosure further includes an electrolyte.

[0075] In some embodiments of the present disclosure, the electrolyte includes a lithium salt and a solvent.

[0076] In some embodiments of the present disclosure, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium difluorophosphate (LiPO2 F 2 ), bis(trifluoromethanesulfonyl)imide lithium LiN (CF 3 SO 2 ) 2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO 2 F) 2 )(LiFSI), LiB(C 2 O 4 ) 2 (LiBOB) or lithium difluorooxalatoborate LiBF 2 (C 2 O 4 )(LiDFOB).

[0077] In some embodiments of the present disclosure, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0078] In some embodiments of the present disclosure, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature performance, etc.

[0079] In some embodiments of the present disclosure, the secondary battery involved in the present disclosure includes the above-mentioned negative electrode plate, positive electrode plate, separator, electrolyte, etc., but is not limited thereto.

[0080] In some embodiments of the present disclosure, the secondary battery involved in the present disclosure may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0081] In some embodiments of the present disclosure, the present disclosure further provides a battery module. The battery module includes the above-mentioned secondary battery. The battery module of the present disclosure uses the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The number of secondary batteries contained in the battery module of the present disclosure can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0082] In some embodiments of the present disclosure, the present disclosure further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0083] In some embodiments of the present disclosure, the present disclosure also provides a device, including but not limited to electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the high power and high energy density requirements of the device for secondary batteries, a battery pack or battery module can be used.

[0084] In some other embodiments of the present disclosure, the device may be a mobile phone, a tablet computer, a laptop computer, etc. The device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0085] The present application is further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application.

[0086] Embodiment and comparative example:

[0087] The positive electrode sheets, separators, and electrolytes used in the secondary batteries prepared in the specific embodiments and comparative examples are as follows:

[0088] The positive electrode sheet uses the ternary material NCM811 positive electrode material. The positive electrode material NCM811, conductive agent SP, carbon nanotubes and binder polyvinylidene fluoride (PVDF) are mixed evenly in a ratio of 96.8:1:0.2:2, coated on an aluminum foil current collector, dried in an oven, and rolled on a roller press to a compaction density of 3.5g / cm 3 , and obtain the required positive electrode sheet.

[0089] The diaphragm is a ceramic-coated polyethylene (PE) film (7um PE base film + 2um ceramic + 2um ceramic).

[0090] The organic solvent selected for the electrolyte is EC:DMC:EMC:FEC=(22:40:30:8). Lithium hexafluorophosphate is dissolved in the organic solvent to prepare an electrolyte with a lithium hexafluorophosphate concentration of 1 mol / L, and then electrolyte additives such as vinyl sulfate (DTD) with a mass fraction of 1% (based on the total mass of the electrolyte) and vinyl carbonate (VC) with a mass fraction of 2% (based on the total mass of the electrolyte) are added and stirred evenly.

[0091] The following are examples and comparative examples of preparing negative electrode sheets:

[0092] Example 1

[0093] The negative electrode sheet is made of silicon oxide-graphite composite material, with silicon oxide accounting for 30% of the negative electrode material by mass. The silicon oxide-graphite negative electrode active material, styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) are mixed in a ratio of 95:1:1.5:1.5, dissolved in a solvent, coated on a copper foil, and then rolled on a roller press to a compaction density of 1.5 g / cm 3 , dried at 110°C in vacuum for 24 hours until the moisture content is 120ppm. An uncoated negative electrode sheet was obtained.

[0094] 5g of lithium carboxylate polyether shown in formula I-1, 1g of lithium difluorooxalate borate (LiDFOB), and 0.005g of initiator (AIBN) were dissolved in 40g of dimethyl carbonate (water content of 40ppm) to prepare a mixed solution with a solid content of 13%, and then the mixed solution was coated on the surface of the uncoated negative electrode plate, vacuum heated to 90°C, and dried for 8h to obtain a negative electrode plate with a mass content of lithium carboxylate polyether of 3%. The negative electrode plate, the positive electrode plate, and the separator were assembled into a small soft pack battery for testing.

[0095]

[0096] Example 2

[0097] The negative electrode sheet is made of silicon oxide-graphite composite material, with silicon oxide accounting for 30% of the negative electrode material by mass. The silicon oxide-graphite negative electrode active material, styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) are mixed in a ratio of 95:1:1.5:1.5, dissolved in a solvent, coated on a copper foil, and then rolled on a roller press to a compaction density of 1.7 g / cm 3 , dried at 110°C in vacuum for 24 hours until the moisture content is 120ppm. An uncoated negative electrode sheet was obtained.

[0098] 5g of lithium carboxylate polyether represented by formula I-2, 1g of lithium tetrafluoroborate (LiBF 4), 0.005g initiator AIBN was dissolved in 40g dimethyl carbonate (water content of 40ppm) to prepare a mixed solution with a solid content of 13%, and then the solution was applied to the surface of the electrode, and then vacuum heated to 100°C and dried for 5h to obtain a negative electrode with a mass content of 5% of carboxylic acid lithium polyether. The negative electrode, positive electrode and separator were assembled into a small soft pack battery for testing.

[0099]

[0100] Example 3

[0101] The negative electrode sheet is made of silicon oxide-graphite composite material, with silicon oxide accounting for 30% of the negative electrode material by mass. The silicon oxide-graphite negative electrode active material, styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) are mixed in a ratio of 95:1:1.5:1.5, dissolved in a solvent, coated on a copper foil, and then rolled on a roller press to a compaction density of 1.6 g / cm 3 , dried at 110°C in vacuum for 24 hours until the moisture content is 120ppm. An uncoated negative electrode sheet was obtained.

[0102] 5 g of lithium carboxylate polyether represented by formula I-3, 1 g of lithium tetrafluoroborate (LiBF 4 ), 0.005g initiator AIBN was dissolved in 50g dimethyl carbonate (water content of 40ppm) to prepare a mixed solution with a solid content of 10.7%, and then the solution was applied to the surface of the electrode, and then vacuum heated to 80°C and dried for 10h to obtain a negative electrode with a mass content of 1% of carboxylic acid lithium polyether. The negative electrode, positive electrode and separator were assembled into a small soft pack battery for testing.

[0103]

[0104] Example 4

[0105] The negative electrode sheet is made of silicon oxide-graphite composite material, with silicon oxide accounting for 30% of the negative electrode material by mass. The silicon oxide-graphite negative electrode active material, styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) are mixed in a ratio of 95:1:1.5:1.5, dissolved in a solvent, coated on a copper foil, and then rolled on a roller press to a compaction density of 1.5 g / cm 3 , dried at 110°C in vacuum for 24 hours until the moisture content is 120ppm. An uncoated negative electrode sheet was obtained.

[0106] 5g of lithium carboxylate polyether shown in formula I-4, 1g of lithium difluorooxalate borate (LiDFOB), and 0.005g of initiator (AIBN) were dissolved in 40g of dimethyl carbonate (water content of 40ppm) to prepare a mixed solution with a solid content of 13%, and then the mixed solution was coated on the surface of the uncoated negative electrode plate, vacuum heated to 90°C, and dried for 8h to obtain a negative electrode plate with a mass content of 3% of lithium carboxylate polyether. The negative electrode plate, the positive electrode plate, and the separator were assembled into a small soft pack battery for testing.

[0107]

[0108] Example 5

[0109] The negative electrode sheet is made of silicon oxide-graphite composite material, with silicon oxide accounting for 30% of the negative electrode material by mass. The silicon oxide-graphite negative electrode active material, styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) are mixed in a ratio of 95:1:1.5:1.5, dissolved in a solvent, coated on a copper foil, and then rolled on a roller press to a compaction density of 1.5 g / cm 3 , dried at 110°C in vacuum for 24 hours until the moisture content is 120ppm. An uncoated negative electrode sheet was obtained.

[0110] 5g of lithium carboxylate polyether shown in formula I-5, 1g of lithium difluorooxalate borate (LiDFOB), and 0.005g of initiator (AIBN) were dissolved in 40g of dimethyl carbonate (water content of 40ppm) to prepare a mixed solution with a solid content of 13%, and then the mixed solution was coated on the surface of the uncoated negative electrode plate, vacuum heated to 90°C, and dried for 8h to obtain a negative electrode plate with a mass content of lithium carboxylate polyether of 3%. The negative electrode plate, the positive electrode plate, and the separator were assembled into a small soft pack battery for testing.

[0111]

[0112] Example 6

[0113] The negative electrode sheet is made of silicon oxide-graphite composite material, with silicon oxide accounting for 30% of the negative electrode material by mass. The silicon oxide-graphite negative electrode active material, styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) are mixed in a ratio of 95:1:1.5:1.5, dissolved in a solvent, coated on a copper foil, and then rolled on a roller press to a compaction density of 1.6 g / cm 3 , dried at 110°C in vacuum for 24 hours until the moisture content is 120ppm. An uncoated negative electrode sheet was obtained.

[0114] 5g of lithium carboxylate polyether represented by formula I-6, 1g of lithium tetrafluoroborate (LiBF 4 ), 0.005g initiator AIBN was dissolved in 24g dimethyl carbonate (water content of 40ppm) to prepare a mixed solution with a solid content of 20%, and then the solution was applied to the surface of the electrode, and then vacuum heated to 80°C and dried for 10h to obtain a negative electrode with a mass content of 1% of carboxylic acid lithium polyether. The negative electrode, positive electrode and separator were assembled into a small soft pack battery for testing.

[0115]

[0116] Example 7

[0117] The negative electrode sheet is made of silicon oxide-graphite composite material, with silicon oxide accounting for 30% of the negative electrode material by mass. The silicon oxide-graphite negative electrode active material, styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) are mixed in a ratio of 95:1:1.5:1.5, dissolved in a solvent, coated on a copper foil, and then rolled on a roller press to a compaction density of 1.6 g / cm 3 , dried at 110°C in vacuum for 24 hours until the moisture content is 120ppm. An uncoated negative electrode sheet was obtained.

[0118] 5 g of lithium carboxylate polyether represented by formula I-7, 1 g of lithium tetrafluoroborate (LiBF 4 ), 0.005g initiator AIBN was dissolved in 194g dimethyl carbonate (water content of 40ppm) to prepare a mixed solution with a solid content of 3%, and then the solution was applied to the surface of the electrode, and then vacuum heated to 80°C and dried for 10h to obtain a negative electrode with a mass content of 1% of carboxylic acid lithium polyether. The negative electrode, positive electrode and separator were assembled into a small soft pack battery for testing.

[0119]

[0120] Example 8

[0121] The negative electrode sheet is made of silicon oxide-graphite composite material, with silicon oxide accounting for 30% of the negative electrode material by mass. The silicon oxide-graphite negative electrode active material, styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) are mixed in a ratio of 95:1:1.5:1.5, dissolved in a solvent, coated on a copper foil, and then rolled on a roller press to a compaction density of 1.6 g / cm 3 , dried at 110°C in vacuum for 24 hours until the moisture content is 120ppm. An uncoated negative electrode sheet was obtained.

[0122] 5g of lithium carboxylate polyether represented by formula I-8, 1g of lithium tetrafluoroborate (LiBF 4 ), 0.005g initiator AIBN was dissolved in 40g dimethyl carbonate (water content of 40ppm) to prepare a mixed solution with a solid content of 13%, and then the solution was applied to the surface of the electrode, and then vacuum heated to 80°C and dried for 10h to obtain a negative electrode with a mass content of 6% of carboxylic acid lithium polyether. The negative electrode, positive electrode and separator were assembled into a small soft pack battery for testing.

[0123]

[0124] Comparative Example 1:

[0125] The negative electrode sheet is made of silicon oxide-graphite composite material, in which silicon oxide accounts for 30% of the mass ratio of the negative electrode material. The silicon oxide-graphite negative electrode material, binder SBR, CMC, and PAA are mixed in a ratio of 95:1:1.5:1.5, coated on the copper foil, dried, and rolled on a roller press. The compaction density is 1.5g / cm 3 , and obtain the required negative electrode sheet. The negative electrode sheet, positive electrode sheet and separator are assembled into a small soft pack battery for testing.

[0126] Preparation of secondary batteries: stack the negative electrode sheet, separator, and positive electrode sheet in order, so that the separator is between the negative electrode sheet and the positive electrode sheet to play an isolating role, and then wind them to obtain a bare battery cell; place the bare battery cell in an outer packaging aluminum-plastic film, inject the above-prepared electrolyte into the dried bare battery cell, and complete the preparation of the secondary battery after vacuum packaging, standing, formation, shaping, capacity testing and other processes.

[0127] Test method:

[0128] The charge and discharge voltage window of the secondary battery is 2.5V-4.2V. Under the condition of 100% SOC, the battery is stored at 60℃ for 7 days to observe the gas production of the soft pack battery.

[0129] The capacity retention rate and capacity recovery rate of the battery were tested before and after storage for 7 days at a high temperature of 55°C. The capacity retention rate = the discharge capacity C after 7 days of high temperature storage. 1 / initial capacity C, capacity recovery rate = discharge capacity C after 7 days of high temperature standing and recharging and discharging 2 / C;

[0130] The cycle performance was tested at a high temperature of 50°C with a current of 1C. The capacity retention rate of 100 cycles at a high temperature of 50°C = discharge capacity of 100 cycles / initial discharge capacity.

[0131] Examples 1-3 and Comparative Example 1 were subjected to electrochemical tests, and the test results are shown in Table 1;

[0132] The contents of the lithium carboxylate polyether are all based on the total mass of the negative electrode material layer.

[0133] [Table 1]

[0134]

[0135] From Comparative Example 1, it can be found that after 7 days at a high temperature of 60°C, the conventional silicon oxide-graphite negative electrode battery cell showed a phenomenon of bloating, while Examples 1-8 did not show a large amount of gas production. During the high temperature cycle process, the cycle performance of Examples 1-8 was greatly improved compared with Comparative Example 1, and the storage performance at a high temperature of 55°C was also better than that of Comparative Example 1.

[0136] Comparison of the experimental results of Examples 1, 4 and 5 shows that when the n and m values ​​of the polymer are changed, the molecular weight of the polymer increases, which changes the fluidity of the polymer mixed solution and its wettability to the electrode, affects the viscosity of the coating slurry, and causes its effect to decrease. When the n and m values ​​decrease, the molecular weight of the polymer decreases, and the number of bifunctional groups at both ends of the carboxylic acid lithium polyether increases, resulting in a larger cross-linking density of the cross-linked network structure formed after polymerization, which is not conducive to the performance of the battery cell.

[0137] In Example 6, the solid content of the polymer mixed solution reached 20%, and its viscosity increased, which affected its wettability in the pole piece, and there were defects on the surface of the negative electrode active material, so there would be a small amount of gas generation. In Example 7, the solid content of the polymer mixed solution was reduced to 3%, which was conducive to the wetting of the pole piece, but in order to meet the requirement of coating a certain mass content of carboxylic acid lithium polyether on the surface of the negative electrode active material, a large amount of mixed solution needed to be coated. The pores of the negative electrode pole piece itself were limited, resulting in the polymer being unable to be completely coated on the surface of the active material, leaving a portion of it on the surface of the negative electrode material layer, which was prone to certain gas generation behavior.

[0138] Although illustrative embodiments have been shown and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present disclosure, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present disclosure.

Claims

1. A negative electrode plate, characterized in that: The negative electrode sheet comprises A negative electrode current collector; and A negative electrode material layer is disposed on the surface of the negative electrode current collector, and the negative electrode material layer comprises a negative electrode active material and lithium carboxylate-based polyether.

2. The negative electrode sheet according to claim 1, wherein: The lithium carboxylate polyether is present on the surface of the negative electrode active material; and / or Based on the total mass of the negative electrode material layer, the mass content of the lithium carboxylate polyether is 0.5%-6%.

3. The negative electrode sheet according to claim 1, wherein: The structure of the lithium carboxylate polyether is shown in Formula I: Among them, n=5-100, m=5-50; R1 and R2 are each independently selected from C2-C20 alkenyl, propylene carbonyl, methyl propylene carbonyl, C2-C3 epoxy; R3, R4, R5 are each independently selected from hydrogen atom, methyl, ethyl.

4. The negative electrode sheet according to claim 3, wherein: The lithium carboxylate polyether comprises at least one of the following structures: Formula I-1 Wherein, n=2-20, m=6-30; Formula I-2 Wherein, n=2-20, m=6-30; Formula I-3 Among them, n=2-20, m=6-30.

5. The negative electrode sheet according to claim 1, wherein: The negative electrode active material comprises at least one of a mixture of silicon dioxide and graphite and a silicon-carbon compound; and / or Based on the total mass of the negative electrode material layer, the mass content of the negative electrode active material is 90% to 96%.

6. The negative electrode sheet according to claim 6, wherein: The mass percentage of silicon oxide in the mixture of silicon oxide and graphite is 5%-40%; and / or The mass proportion of silicon in the silicon-carbon compound is 5%-40%.

7. A method for preparing the negative electrode sheet according to any one of claims 1 to 6, characterized in that: The method comprises S1: mixing a binder, a solvent and a negative electrode active material, and then coating the mixture on the surface of a negative electrode current collector to obtain a negative electrode sheet that does not include a lithium carboxylate polyether; S2: rolling the negative electrode sheet obtained in step S1 and drying it; S3: mixing carboxylic acid lithium polyether, lithium salt, initiator and solvent, and then coating the mixture on the surface of the negative electrode sheet obtained in step S2 away from the current collector, and drying to obtain the negative electrode sheet.

8. The method for preparing a negative electrode sheet according to claim 7, characterized in that: The preparation process satisfies at least one of the conditions 1) to 4): 1) The compacted density is 1.5 g / cm 3 -1.7g / cm 3 ; 2) The solvent in step S3 includes at least one of methyl formate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, butyl acetate, ethyl butyrate, dimethyl ether, butyl ether, toluene, and acetonitrile; 3) The solid content of the mixed solution is 3%-20%; 4) The drying in step S3 is vacuum drying at a drying temperature of 60°C-110°C.

9. A secondary battery, characterized in that: The secondary battery comprises the negative electrode sheet according to any one of claims 1 to 6 or the negative electrode sheet prepared by the preparation method according to any one of claims 7 to 8.

10. A device, characterized in that: The device comprises the secondary battery according to claim 9.